Engineering neuroblastoma models for clinical translation - Taiyu Song; Rui Liu; Feika Bian; Bin Kong; Jingjing Gan (Engineered Regeneration, 2025)
Neuroblastoma is a profoundly heterogenous extracranial solid tumor in pediatric patients. Elevated risk grade of neuroblastoma has been correlated with unsatisfactory prognosis and resistance to chemotherapy. Despite multimodal therapies exploited for killing neuroblastoma tumor cells, in high-risk neuroblastoma patients, the long-term survival is currently less than 50%. Promising approaches to evaluating the extent of heterogeneity via gene expression profiling of cell subpopulations within individual tumors are still lacking. There is uncertainty about the cross-talk between neuroblastoma cells and other non-neoplastic cell components in the tumor microenvironment. Recently, concerns about individualized eradication therapies have advanced the demand for the diversified construction of neuroblastoma tumor models. This review briefly introduces the genetic variation, subpopulations, and tumor microenvironment aspects of neuroblastoma heterogeneity. Then, we summarize recent methods of constructing tumor models to mimic the biological features of neuroblastoma tumors in vitro. Finally, we conclude the future trends and perspectives in neuroblastoma tumor therapy.